Effect of beeswax edible film on preservation of Naem product quality during storage - Bui, Duyen; Tangkham, Wannee; LeMieux, Frederick; Vuong, Oanh; Prinyawiwatkul, Witoon; Xu, Zhimin (Agriculture and Natural Resources, 2024)
Importance of the work: Beeswax (BW) could be a natural ingredient applied in edible packing film to effectively extend the shelf-life of Thai fermented sausage (‘Naem’). Objective: To evaluate the capability of edible films made from beeswax in extending the shelf-life of Naem. Materials & Methods: Naem samples were wrapped using one of four different film groups: polyvinyl chloride (PVC) or 0%, 1% or 3% BW. Changes were determined and compared in the pH, moisture content, color (L*, a* and b*), lipid oxidation and aerobic plate count (APC) and growth rates of lactic acid bacteria, Escherichia coli, Enterobacteriaceae, Staphylococcus spp. and Salmonella spp. in the Naem samples of the four groups during refrigerated storage. Results: The 1% and 3% BW groups had significantly higher pH, L* and b* values after storage for 15 d than the PVC and 0% BW groups. The moisture content in the PVC group was significantly higher than in the other three groups. Naem in the 1% or 3% BW group had the lowest lipid oxidation level at 1.13 mg malondialdehyde/kg at an initial storage stage and still maintained a lower level after storage for 15 d. Additionally, their APC counts were significantly lower than for the PVC and 0% groups during storage. No Enterobacteriaceae were detected in the 3% BW group, while E. coli, Staphylococcus spp. and Salmonella spp. were not found in all groups after storage for 15 d. Main finding: The edible film made from 3% BW significantly improved the shelf-life of Naem, with fewer changes in color, lipid oxidation, and microbial growth.